Testing Polish Secondary-School Students’ Written Social Communication Competence Based on a Timed Composition Task - Gołata Krzysztof (Marketing of Scientific and Research Organizations, 2022)
This study experimentally evaluated Polish school students’ competence at written communication, understood as one of the forms of social communication. The task, performed online, was designed to see if the students were able to select the most important information from a given base text and to compose new texts on this basis to comply with three different length requirements, and how they behaved under the pressure of the time allocated to complete the sub-tasks. Results from an overall pool of 500 secondary school students from a diverse sample of schools (in the city of Poznań and the surrounding Wielkopolska province) that differed in terms of type and ranking suggest an overall poor competence at various composite skills involved in written social communication: information selection, summarization, logical structuring, and cohesive embellishment. Participants clearly exhibited various problems with concisely formulating thoughts, properly complying with instructions, etc. Composing a short, written message (based on a provided base text) and/or freely embellishing and reformulating information clearly caused them considerable difficulty. The article closes with some suggestions for how the methods used could potentially be improved in future studies of this type.